A Pyridinium–Urea‐Coupled Polyether Receptor for the Selective Sensing of Lysine and Cell Imaging. Issue 2 (16th December 2016) - Ghosh, Kumaresh; Tarafdar, Debojyoti; Petsalakis, Ioannis D.; Theodorakopoulos, Giannoula
Abstract : The pyridinium‐based polyether‐tethered receptor1 with a naphthalene fluorophore has been established as a fluororeceptor for the selective sensing of lysine over a series of other amino acids. The receptor1 exhibits significantly increased fluorescence intensity upon interaction with lysine in CH3 CN/H2 O [4:1 v/v, pH 7.4, 10 mm 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid (HEPES) buffer]. In contrast, the model compound2, which is devoid of a polyether unit, interacts with both lysine and valine and shows emission changes at different wavelengths. Receptor1 was successfully applied for the detection of lysine in the cellular environment through fluorescent imaging. Abstract : The pyridinium–urea‐coupled polyether receptor1 with a naphthalene fluorophore is a fluororeceptor for the selective sensing of lysine over a series of other amino acids. The receptor exhibits significantly increased fluorescence intensity upon interaction with lysine in CH3 CN/H2 O. Furthermore, receptor1 responds to lysine in the cellular environment.